Developing clinical skills bundles. (5th June 2015) - Mok, May; Ker, Jean
Summary: Background: This article describes an innovative method of learning clinical skills. A care bundle is defined as a small set of evidence‐based interventions that, when implemented together, results in significantly better patient outcomes than when implemented individually. Care bundles improve the consistency of standards of care delivered, and hence reduce harm. Context: In 2007 The Scottish Clinical Skills Strategy identified the use of simulation‐based education to ensure all health care staff can deliver a consistently high standard of clinical skills practice throughout the National Health Service in Scotland (NHS Scotland). Innovation: Clinical skills bundles were developed to underpin a number of evidence‐based care bundles. Grouping the clinical skills together and learning them as a clinical skills bundle may improve the reliability of skills delivery for each care bundle. Three groups were recruited and asked to identify a consensus of the essential technical and non‐technical skills for clinical skills bundle for a central venous catheter (CVC) maintenance care bundle. As a pilot, six clinical skills bundle workshops were held for junior doctors, nursing and medical students, and clinical skills educators. The aims of the workshops were to introduce the concepts of clinical skills bundles and to give participants a chance to practice the underpinning clinical skills bundle for a care bundle using simulation. The majority of participants rated the workshop as excellent or good. Self‐reported learning included refreshing their clinical skills in a different context. Care bundles improve the consistency of standards of care delivered Implication: Learning skills together as a bundle may enhance the reliability of clinical skills performance for care bundles, and may also reinforce the use of care bundles.